Composition, in vitro digestibility, and sensory evaluation of extruded whole grain sorghum breakfast cereals. Issue 1 (June 2015) - Mkandawire, Nyambe L.; Weier, Steven A.; Weller, Curtis L.; Jackson, David S.; Rose, Devin J.
Abstract: Two sorghum genotypes (red, tannin; white, non-tannin), were evaluated for their potential use in breakfast cereals. Two levels of whole grain sorghum flour (550 g/kg dry mix or 700 g/kg dry mix) were processed per genotype using a pilot-scale, twin screw extruder. A whole grain oat-based cereal was used as a reference. White sorghum cereals (WSC) had significantly (p < 0.05) higher starch, brightness (L*), and yellowness (b*) than red sorghum cereals (RSC). RSC had higher protein and bulk density than the WSC. Cereals made with 700 g sorghum flour/kg were smaller and denser with lower water solubility and absorption indices than those made with 550 g/kg. In vitro protein digestibility of the RSC (43–58%) was significantly reduced compared with the WSC (69–73%) and the reference sample (72%). WSC with 700 g sorghum flour/kg contained significantly more resistant starch than the RSC cereals and the oat reference (208 g/kg starch versus 81–147 g/kg starch, respectively). Overall acceptability and texture of sorghum cereals did not differ significantly from the oat reference, although appearance and aroma liking were significantly reduced. Therefore, non-tannin sorghum has potential to be used in the breakfast cereal industry with minimal impact on nutritional profile and sensory properties. Highlights: Tannin and non-tannin whole grain sorghum at two formulation levels were extruded. Tannin-containing cereals had low in vitro protein digestibility. Non-tannin cereal with 700 g sorghum flour/kg cereal had the most resistant starch. Non-tannin cereals were generally more liked by panelists than tannin cereals. Non-tannin sorghum may be used in whole grain extruded breakfast cereals.